Health, Education and Occupational Status of Deshi Muslims - Dr. Abdul Wakil Ali (International Journal of Advanced Science and Technology, 2020)
Health, education and occupation have been considered as a human well-being concept with its core being the capability approach. The objective of this research was to capture the status of human development for the Deshi Muslims people living in the selected area. This research employed a purposive multi-stage random sampling technique and use of 250 sample households of Rangjuli, Matia and Lakhipur community development blocks comprising 83, 83 and 84 households respectively, which were 10 per cent of total Deshi Muslims households. The research found that the human development index which comprises health, education and occupation or income of the sample community development blocks with a small variation ranging from 0.426 to 0.478 comprising the total human development index value at 0.450 which was lower than the state level of 0.557. The difference in human development index value among community development blocks was due to the differences in availability of educational institutions, health facilities and earning avenues. The human development index of the Deshi Muslims was a gloomy condition. The human development index value of education and health was found below than state average .However, in respect to income the human development index value was a slightly higher than the state average. The findings imply that there was a shortfall in the expansion of human capability in case of Deshi Muslims living in the sample area of the Goalpara district.